FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TENAGA LISTRIK KONSUMEN INDUSTRI KECIL PT PERUSAHAAN LISTRIK NEGARA (PERSERO) - Aminuddin, Aminuddin (IQTISHODUNA, 2011)
This research is analysis of electricity demand, and focus for small industry sector in PT Perusahaan listrik Negara (Persero) or PT PLN (Persero). Dependent variable is demand electricity or kWh sales, and independent variable consist of install capacity, average tariff, and rate of capacity using percustomers. Step of research and process result based on SPSS calculation, and use cross section data on January 2010. Obtain result that install capacity has given positif impact, and average tariff and rate of capacity using percustomers has given negative impact. All of that independent variable has significant influence to electricity demand of small industry sector. PLN’s management has to observe growth of explanatory variable to make policy for demand and supply equilibrium and toward customers satisfaction.